Cost-effectiveness of lenalidomide plus dexamethasone vs bortezomib plus melphalan and prednisone in transplant-ineligible US patients with newly-diagnosed multiple myeloma. (3rd March 2016) - Usmani, S. Z.; Cavenagh, J. D.; Belch, A. R.; Hulin, C.; Basu, S.; White, D.; Nooka, A.; Ervin-Haynes, A.; Yiu, W.; Nagarwala, Y.; Berger, A.; Pelligra, C. G.; et al.
Abstract: Objective: To conduct a cost-effectiveness assessment of lenalidomide plus dexamethasone (Rd) vs bortezomib plus melphalan and prednisone (VMP) as initial treatment for transplant-ineligible patients with newly-diagnosed multiple myeloma (MM), from a US payer perspective. Methods: A partitioned survival model was developed to estimate expected life-years (LYs), quality-adjusted LYs (QALYs), direct costs and incremental costs per QALY and LY gained associated with use of Rd vs VMP over a patient's lifetime. Information on the efficacy and safety of Rd and VMP was based on data from multinational phase III clinical trials and a network meta-analysis. Pre-progression direct costs included the costs of Rd and VMP, treatment of adverse events (including prophylaxis) and routine care and monitoring associated with MM. Post-progression direct costs included costs of subsequent treatment(s) and routine care and monitoring for progressive disease, all obtained from published literature and estimated from a US payer perspective. Utilities were obtained from the aforementioned trials. Costs and outcomes were discounted at 3% annually. Results: Relative to VMP, use of Rd was expected to result in an additional 2.22 LYs and 1.47 QALYs (discounted). Patients initiated with Rd were expected to incur an additional 78, 977 in mean lifetime direct costs (discounted) vs those initiated with VMP. The incremental costs per QALY and per LY gained with Rd vs VMP were 53, 826 and 35, 552, respectively. In sensitivity analyses, results were found to be most sensitive to differences in survival associated with Rd vs VMP, the cost of lenalidomide and the discount rate applied to effectiveness outcomes. Conclusions: Rd was expected to result in greater LYs and QALYs compared with VMP, with similar overall costs per LY for each regimen. Results of this analysis indicated that Rd may be a cost-effective alternative to VMP as initial treatment for transplant-ineligible patients with MM, with an incremental cost-effectiveness ratio well within the levels for recent advancements in oncology.